Chromosome Characterization of Bartek (Cucumis Melo L. var. Bartek), Local Melon Variety from Pemalang - Setiadi Daryono and Dian Aruni Kumalawati, Budi (Jurnal Ilmu Pertanian, 2013)
ABSTRACTBartek is one of local melon varieties which mainly cultivated in Pemalang, Central Java. Bartek has three shapes of fruit variation; Long-Green, Ellipse-Green, and Yellow. Chromosome characterization of the Bartek was investigated to determine the genetic variation. The main purpose of this research was to determine the genetic characters of Bartek including chromosome number, mitosis, cell cycle, and karyotype. Squash method was used for chromosome preparation. The results showed that all of Bartek observed in this study have similar diploid (2n) chromosome number = 24. According to total number of chromosome, Bartek is more related to melon. The mitotic analysis exhibited that the Bartek has same Karyotype formula, 2n = 2x = 24m. According to the R value of the three kind of Bartek (R< 0.27), it has indicated that three kind of Bartek were considered to be originated from same species and one of melon varieties (Cucumis melo L. var. Bartek).Key words: cucumber, bartek, chromosome, karyotype